Increased glutarate production by blocking the glutaryl-CoA dehydrogenation pathway and a catabolic pathway involving l-2-hydroxyglutarate - Zhang, Manman (Nat Commun, 2018)
Glutarate is a five carbon platform chemical produced during the catabolism of l-lysine. It is known that it can be catabolized through the glutaryl-CoA dehydrogenation pathway. Here, we discover that Pseudomonas putida KT2440 has an additional glutarate catabolic pathway involving l-2-hydroxyglutarate (l-2-HG), an abnormal metabolite produced from 2-ketoglutarate (2-KG). In this pathway, CsiD, a Fe(2+)/2-KG-dependent glutarate hydroxylase, is capable of converting glutarate into l-2-HG, and LhgO, an l-2-HG oxidase, can catalyze l-2-HG into 2-KG. We construct a recombinant strain that lacks both glutarate catabolic pathways. It can produce glutarate from l-lysine with a yield of 0.85 mol glutarate/mol l-lysine. Thus, l-2-HG anabolism and catabolism is a metabolic alternative to the glutaryl-CoA dehydrogenation pathway in P. putida KT2440; l-lysine can be both ketogenic and glucogenic.